Conversation Method in Indigenous Research - Kovach, Margaret (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
In reflecting upon two qualitative research projects incorporating an Indigenous methodology, this article focuses on the use of the conversational method as a means for gathering knowledge through story. The article first provides a theoretical discussion which illustrates that for the conversational method to be identified as an Indigenous research method it must flow from an Indigenous paradigm. The article then moves to an exploration of the conversational method in action and offers reflections on the significance of researcher-in-relation and the inter- relationship between this method, ethics and care.